2019
DOI: 10.1186/s12939-019-1085-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study of “real world” implementation of a clinical poverty tool in diverse family medicine and pediatric care settings

Abstract: BackgroundPoverty is associated with increased morbidity related to multiple child and adult health conditions and increased risk of premature death. Despite robust evidence linking income and health, and some recommendations for universal screening, poverty screening is not routinely conducted in clinical care.MethodsWe conducted an exploratory study of implementing universal poverty screening and intervention in family medicine and a range of pediatric care settings (primary through tertiary). After attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Although physicians welcomed screening tools, the authors noted that screening was likely not feasible if the physician was solely responsible, and recommended a team based approach (14). A recent study of universal screening in "real world" primary care settings reported that 9% of patients had been screened (24). Participating physicians were self-selected early adopters, committed to the process; 28% of patients screened positive, possibly indicating some targeting of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although physicians welcomed screening tools, the authors noted that screening was likely not feasible if the physician was solely responsible, and recommended a team based approach (14). A recent study of universal screening in "real world" primary care settings reported that 9% of patients had been screened (24). Participating physicians were self-selected early adopters, committed to the process; 28% of patients screened positive, possibly indicating some targeting of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Canada, screening for poverty is not currently a routine part of family practice, with some exceptions (23). Barriers include lack of provider training, lack of time, lack of knowledge and expertise, and di culty changing work ows (24,25). There may be multiple competing priorities as family physicians look after many issues and conditions that require attention.…”
Section: Contributions To Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Data 5 from 22 Canadian healthcare professionals have suggested that using the question 'Do you have difficulty making ends meet at the end of the month?' is acceptable to 75% of those patients who responded to the questionnaire (n = 56, 100% response rate).…”
Section: The Case To Screenmentioning
confidence: 99%
“…However, in Canada, screening for poverty is not currently a routine part of family practice, with some exceptions (23). Barriers include lack of provider training, lack of time, lack of knowledge and expertise, and di culty changing work ows (24,25). There may be multiple competing priorities as family physicians look after many issues and conditions that require attention.…”
Section: Contributions To Literaturementioning
confidence: 99%